Penerapan Analisis Gaya Kepemimpinan Dan Kinerja Pada Pt. Arya Lingga Manik Cabang Panorma Bali Residance Ciseeng Kabupaten Bogor - Mitri Nelsi; Irfan Rizka Akbar (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the application of leadership style and performance analysis at PT. Arya Lingga Manik, Panorama Bali Residance Branch, Ciseeng, Bogor Regency. The method used is a qualitative approach using a sampling technique, namely purposive sampling. Data collection techniques in this study used structured and unstructured interviews, observation, and documentation. Data analysis techniques in this study used SWOT analysis, observation, and direct interviews with key informants and informants. The results of this study indicate that the application of the leadership style applied at PT. Arya Lingga Manik Branch of Panorama Bali Residance, Ciseeng-Bogor is a collective leadership style where there is no longer decision-making from a Leader himself as before, but must go through the approval of other parties such as the Admin, and other relevant employee staff. While the leadership performance at PT. Arya Lingga Manik was said to be good because in the results of interviews with informants, after changing leadership styles, the company's employee performance increased or the leadership held training for staff to improve skills and listen more to the opinions of their subordinates.